Customer satisfaction and corporate investment policies - Vo, Lai Van; Le, Huong Thi Thu; Le, Danh Vinh; Phung, Minh Tuan; Wang, Yi-Hsien; Yang, Fu-Ju (Journal of Business Economics and Management, 2017)
This paper examines the effect of satisfaction with firms’ products and services on their capital investment policies. Using data from the American Customer Satisfaction Index from 1994 to 2013, the results of the regression models show that firms with higher customer satisfaction will invest more heavily in capital expenditures in the future. The results further show that this positive effect is more pronounced for firms with less growth opportunities or a high cost of capital. This would include those firms with low market-to-book ratios, young and small firms, or firms in more competitive industries. Overall, this study argues that customer satisfaction is an important factor affecting the firm’s investment policy. The findings provide a better understanding of the role of customer satisfaction which can generate growth opportunities, reduce cost and motivate a firm to invest more in capital.